Mesenchymal Stem/Stromal Cells from Discarded Neonatal Sternal Tissue: In Vitro Characterization and Angiogenic Properties - Shuyun Wang; Lakshmi Mundada; Eric Colomb; Richard G. Ohye; Ming-Sing Si (Stem Cells International)
Autologous and nonautologous bone marrow mesenchymal stem/stromal cells (MSCs) are being evaluated as proangiogenic agents for ischemic and vascular disease in adults but not in children. A significant number of newborns and infants with critical congenital heart disease who undergo cardiac surgery already have or are at risk of developing conditions related to inadequate tissue perfusion. During neonatal cardiac surgery, a small amount of sternal tissue is usually discarded. Here we demonstrate that MSCs can be isolated from human neonatal sternal tissue using a nonenzymatic explant culture method. Neonatal sternal bone MSCs (sbMSCs) were clonogenic, had a surface marker expression profile that was characteristic of bone marrow MSCs, were multipotent, and expressed pluripotency-related genes at low levels. Neonatal sbMSCs also demonstrated in vitro proangiogenic properties. Sternal bone MSCs cooperated with human umbilical vein endothelial cells (HUVECs) to form 3D networks and tubes in vitro. Conditioned media from sbMSCs cultured in hypoxia also promoted HUVEC survival and migration. Given the neonatal source, ease of isolation, and proangiogenic properties, sbMSCs may have relevance to therapeutic applications.